PEMBERDAYAAN MASYARAKAT MELALUI OPTIMALISASI POTENSI BUAH SALAK DI SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - Ridwan, Muhamad; Khusnul Rifani, Siti; Ahmad Nurcahya, Mukti; Habibatur Rahman, Fathi; Muhammad Hasan, Zulfikar; Alvin Mubarok, Alvian (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
Behind the fertility of salak plantations in Sleman Regency, Special Region of Yogyakarta, there are several problems, including 1) fluctuations in the price of salak fruit; 2) the threat of the Mount Merapi eruption; 3) post-eruption economic recovery; and 4) a lack of innovation to optimize the potential of salak plantations. Kembangarum village is one of the areas in Sleman Regency that needs guidance in optimizing the potential of salak fruit on the slopes of Mount Merapi. The program was designed to empower the community by training residents to process salak fruit, peels, and seeds into various products. The method was through field coordination, preparation of tools and materials, program outreach, training, and mentoring, and ended with program evaluation. The program was implemented for five months and has achieved some progress. First, a learning house for residents to produce processed salak has been formed. Second, the creation of residents skilled in processing fruit, peels, and seeds of salak into various processed products with higher selling value with an increase in sales turnover of around 24%. Third, creating pilots for the residents' home industry, along with an offline and online marketing guide, can improve the economic standard of the residents.